Respuesta :

Answer:

[tex]5\left(y+5z\right)\left(y-5z\right)[/tex]

Step-by-step explanation:

[tex]\mathrm{The \;given \;equation \;is \; 5y^2-125z^2}[/tex]

[tex]\mathrm{Factor\:out\:common\:term\:}5:\quad 5\left(y^2-25z^2\right)\\\\= 5\left(y^2-25z^2\right)[/tex]

[tex]\left y^2-25z^2\right[/tex]
[tex]25z^2 = \left(5z\right)^2[/tex]
==> [tex]\left y^2-25z^2\right = y^2-\left(5z\right)^2[/tex]

[tex]\mathrm{Apply\:Difference\:of\:Two\:Squares\:Formula:\:}x^2-y^2=\left(x+y\right)\left(x-y\right)[/tex]
[tex]y^2-\left(5z\right)^2=\left(y+5z\right)\left(y-5z\right)[/tex]

So the factored expression is
[tex]5\left(y+5z\right)\left(y-5z\right)[/tex]